Mm-wave polarimeter and profilometry design study for retrieving plasma density in the PANDORA experiment - Torrisi, G.; Naselli, E.; Mascali, D.; Di Donato, L.; Sorbello, G. (Frontiers in Astronomy and Space Sciences, 2022)
In the recent past, the possibility to use a superconducting trap confining a hot and dense plasma as a tool to investigate radioactivity in astrophysical scenarios has been proposed. Making possible these kind of unprecedented measurements is the main aim of the PANDORA (Plasmas for Astrophysics Nuclear Decays Observation and Radiation for Archaeometry) project. In this context, it is planned to build a compact and flexible magnetic plasma trap where plasma reaches an electron density ne ~ 1E11 - 1E13 cm^-3, and an electron temperature, in units of kT, kTe ~ 0.1 – 30 keV. The setup is conceived to be able to measure, for the first time, nuclear beta-decay rates in stellar-like conditions in terms of ionization states. In this paper, the design study of a mm-wave interferometer - polarimeter for the PANDORA plasma line-integrated electron density measurement is presented. The paper highlights the method and the challenges of this type of measurements for the first time proposed for a magneto-plasma trap which represents an “intermediate” case between the ultra-compact plasma ion sources and the large-size thermonuclear fusion devices. Preliminary measurements at scaled microwave frequencies have carried out both on a "free-space'' setup by using a wire-grid polarizer and a rotable Ka-band OMT+horn antennas system, and on a compact trap (called Flexible Plasma Trap) installed at INFN-LNS and used as PANDORA down-sized testbench are described. The interferopolarimeter technique will support beta-decay investigation by simultaneous measurements of the total plasma density, which is crucial to carefully evaluate the decay-constant and to extrapolate the laboratory observed data to the astrophysical scenarios. Moreover, this work proposes to adopt an electromagnetic inverse-scattering-based technique-based method to retrieve the electron density profile along the probing antennas line-of-sight. Numerical results of this so-called "inverse profilometry'' are also shown.